Konsep dan Implementasi Maisir, Gharar, serta Riba: Tinjauan Dalil dan Perspektif Lintas Agama - Derendra Uziel Sachio; Muhammad Ibrahim; Nabiilah Afraa Naa’ilah; Raffly tama Haqqin; Siti Nur Adni; Tita Muthiara Sari; Ummu Aisyah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study examines in depth the concepts of maysir, gharar, and riba as three practices that are prohibited in sharia economics because they are considered to cause injustice and imbalance in economic activities. Through an analysis of the postulates of the Qur'an and Hadith, this study confirms that the prohibition of maysir is based on the element of excessive speculation that harms one of the parties, gharar is rejected because it contains ambiguity in the object and contract, while riba is prohibited because it creates an unequal addition in financial transactions. In addition, the study highlights how other religions and various modern economic systems have paid attention to the principles that are in line with the prohibition of these three concepts, especially related to business ethics, social justice, and economic risk mitigation. A cross-faith perspective shows that universal values such as honesty, transparency, and balance are essential foundations for building a sustainable economic order. By combining normative perspectives and cross-tradition comparisons, this study seeks to provide a comprehensive understanding of the dangers of maysir, gharar, and usury, as well as the implications of the implementation of their prohibition in modern economic life. The results of the study are expected to be a reference in formulating economic practices that are fair, stable, and able to be widely applied in various communities.